Immunogenicity Test of ESAT-6/CFP-10 Mycobacterium tuberculosis (Indonesian Strain) Recombinant Protein Fusion: TNF-α, IL-17 and CD4+ T Cells Expression in PBMC Culture - Eko Prasetyo; Triwahju Astuti; Nunuk Sri Muktiati; Maimun Z Arthamin (Jurnal Respirologi Indonesia, 2019)
Background: Bascillus Calmette Guѐrin vaccination has not provided protection against TB in adults. ESAT-6/CFP-10 Mtb recombinant protein fusion as a vaccine candidate can stimulate the body's immune response. Interleukin-17, TNF-α and CD4+ play a major role against TB. This study aims to determine that the recombinant protein fusion ESAT-6/CFP-10 Mtb can stimulate TNF-α, IL-17 and CD4+ T cells expression in PBMC culture. Methods: Design of this study is experimental study. Number of research sample per group of 8 subjects. The subjects: healthy, TB contact and TB patients were taken their peripheral blood sample and treated with ESAT-6/CFP-10 Mtb recombinant protein fusion. TNF-α CD4+ T cells were measured by ELISA. Flow cytometry is used to measure IL-17 and CD4+ Tcells. As standard protocol research on tuberculosis vaccine, each subject also treated without antigen and with PPD. Results: There was no significant increase in the administration of ESAT-6/CFP-10 Mtb fusion compared without antigen on TNF-α expression of CD4+ (P=0.202), expression of IL-17 CD4+ (P=0.994) and percentage of CD4+ T cells (P=0.183). ESAT-6/CFP-10 Mtb Fusion was able to stimulate expression of TNF-α CD4+ in healthy subjects (29.91±1.23pg/ml), TB contact (32.21±4.02pg/ml) and TB patients (33.35±8.41 pg/ml). Expression IL-17 CD4+ in healthy subjects (33.24 ± 39.01%), TB contact (23.88 ± 21%) and TB patients (51.93 ± 36%). CD4+ T cell expression in healthy subjects 30.64 ± 7.63%, TB contact 24.58 ± 5.24% and TB patients (40.73±2.63%). Conclusions: ESAT-6/CFP-10 Mtb recombinant proteins fusion may stimulate the production of TNF-α, IL-17 CD4+ and CD4+ T cells in all subject. Expression of TNF-α, IL-17 CD4+ and CD4+ T cells in the healthy group, indicated that the ESAT-6/CFP-10 recombinant protein fusion has the potential as vaccine candidate. (J Respir Indo. 2019; 39(3):160-8)